Saint Peter Chrysologus versus “Arius … the pitiful man” - BOICU, Dragoș (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2025)
This paper focuses on a witness to the gradual consolidation of the authority of the Council of Nicaea, in the form we know it today, namely Saint Peter Chrysologus. In his homilies delivered before the Christians of Ravenna, he draws attention to the Arian teachings which, even a hundred years after the condemnation of Arius, continued to spread and deeply divide the Church. In his polemic against Arianism, Saint Peter Chrysologus appeals to elementary logic, affirming that the attributes “Father” and “Almighty” are sufficient to believe that God has, from eternity, possessed the quality of Fatherhood in relation to the coeternal Son.